2023
DOI: 10.3390/medicina59030479
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Liver Fibrosis Using 2D-SWE Liver Ultrasound Elastography and Dynamic Liver Scintigraphy with 99mTc-mebrofenin: A Comparative Prospective Single-Center Study

Abstract: Background and Objectives: Many quantitative imaging modalities are available that quantify chronic liver disease, although only a few of them are included in clinical guidelines. Many more imaging options are still competing to find their place in the area of diagnosing chronic liver disease. We report our first prospective single-center study evaluating different imaging modalities that stratify viral hepatitis-associated liver fibrosis in a treatment-naïve patient group. Materials and Methods: The aim of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(80 reference statements)
0
0
0
Order By: Relevance
“…Liver stiffness is one of the most important indicators of liver disease, as changes in liver stiffness often accompany the progression of liver disease [1]. Studies have shown that approximately 12% of dogs have varying degrees of hepatic fibrosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Liver stiffness is one of the most important indicators of liver disease, as changes in liver stiffness often accompany the progression of liver disease [1]. Studies have shown that approximately 12% of dogs have varying degrees of hepatic fibrosis [2].…”
Section: Introductionmentioning
confidence: 99%